2024
DOI: 10.1001/jamanetworkopen.2024.3345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Epidemiologic, and Pathologic Significance of ERBB2-Low Expression in Breast Cancer

Thaer Khoury,
Lucas Mendicino,
Rochelle Payne Ondracek
et al.

Abstract: ImportanceIt is unclear whether breast cancer (BC) with low ERBB2 expression (ERBB2-low) is a distinct clinical, pathological, and epidemiological entity from BC classified as no ERBB2 expression (ERBB2-negative).ObjectiveTo evaluate the clinical, pathological, and epidemiologic features of BC with ERBB2-low expression compared with ERBB2-negative BC in a large population study.Design, Setting, and ParticipantsThis cohort study was conducted as part of the Pathways Study, a prospective, racially and ethnically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…In a most recently published prospective cohort study that was not yet included in the systematic reviews and meta-analyses described above, HER2-low had a positive impact on survival also in HR-negative patients (HR 0.54, 95% CI 0.33–0.91, P = 0.02) irrespective of other key covariates (HR 0.48, 95% CI 0.27–0.83, P = 0.009) [ 18 ]. The authors concluded that these findings raised the possibility that HER2-low breast cancer may be a unique entity.…”
mentioning
confidence: 99%
“…In a most recently published prospective cohort study that was not yet included in the systematic reviews and meta-analyses described above, HER2-low had a positive impact on survival also in HR-negative patients (HR 0.54, 95% CI 0.33–0.91, P = 0.02) irrespective of other key covariates (HR 0.48, 95% CI 0.27–0.83, P = 0.009) [ 18 ]. The authors concluded that these findings raised the possibility that HER2-low breast cancer may be a unique entity.…”
mentioning
confidence: 99%